Synthesis, Spectroscopic, and Photophysical Studies of Phosphorescent Bis(2-(2,4-difluorophenyl)pyridine)Iridium(III) Complex Containing Derivative of 1H-1,2,4-Triazole Anchillary Ligand - Nurul Husna As Saedah Bain; Noorshida Mohd Ali; Yusnita Juahir; Norhayati Hashim; Illyas Md Isa; Azmi Mohamed; Azlan Kamari; Bohari Mohd Yamin (Universitas Gadjah Mada, 2021)
A cationic complex of iridium(III), [Ir(2,4-F2ppy)2(F2bpyta)]PF6 utilizing 1,2,4-triazolepyridyl as an anchillary ligand modified with a 2,6-difluorobenzyl substituent was synthesized and characterized. The aromatic signals of pyridyltriazole and phenylpyridine proton were detected in the 1H-NMR spectrum between 10.00 and 7.00 ppm. Only one singlet peak was detected at 8.46 ppm H(8) shifted to the upfield, demonstrating that C5 was coordinated to the central iridium metal. The bands exhibited in the range of 1555–1431 cm–1 in the IR spectrum because of the C=C and C=N aromatic rings stretching pyridine, phenyl, and triazole vibrations. The UV-Vis absorption spectrum showed a slight and broad absorbance peak at lower energy at a lmax = 371 nm (e = 6129 M−1 cm−1) in the visible range due to 1MLCT and 3MLCT transitions. Blue emission was observed in the steady-state emission spectral of [Ir(2,4-F2ppy)2(F2bpyta)]PF6 and the other two previously synthesized iridium(III) complexes in CH2Cl2 solutions (air-equilibrated) at room temperature. The spectrum of luminescence for the [Ir(2,4-F2ppy)2(F2bpyta)]PF6 (lem = 461 nm) is blue-shifted when compared to the [Ir(2,4-F2ppy)2(hpyta)]PF6 (lem = 469 nm), but red-shifted when related to the [Ir(2,4-F2ppy)2(mbpyta)]PF6 (lem = 454 nm).